Sistem Pelayanan Humas Universitas Islam Negeri Sumatera Utara Dalam Membangun Citra Universitas Islam Negeri Sumatera Utara - Lia Mardiah (Jurnal Ilmu Komunikasi PROGRESSIO, 2021)
Public Relations service system of the North Sumatera State Islamic University in building the image of the North Sumatera State Islamic University .Service system is according to the meaning of the word, system is a regular way of procedures to do something. The service system is actually a unit of factors needed in the implementation of a service system. The service system also at the event is a framework of interconnected procedures and methods, which are arranged according to a comprehensive scheme to carry out an activity or main function of the company produced by a particular process that aims to provide information, provide services by fulfilling public interest in creating good services with processes in the service system. Helping the day-to-day decision making of the company's operations management as well as providing appropriate information to share.The purpose of this study is to see the Public Relations Service System of the State Islamic University of North Sumatra in Building the Image of the State Islamic University of North Sumatra. This study uses the theory of image and service quality proposed by Frank Jefkins and Mardi Jhon Harrowitz, while the theory of service quality by Ridwan and Sudarajat and Bharata. The method in this study used a qualitative descriptive approach with data observation techniques, interviews, and documentation. The results of the study indicate that the public relations service system of the State Islamic University of North Sumatra provides a positive image to the community.